2017
DOI: 10.14295/oh.v23i2.972
|View full text |Cite
|
Sign up to set email alerts
|

Management of corm size and soil water content for gladiolus flower production

Abstract: Gladiolus grandiflorus Andrews, in the family Iridaceae, is one of the most produced and marketed flowers in the world. In general, however, research results on gladioli production factors are scarce and divergent. The objective of this work was to evaluate the influence of corm size and soil water content on gladiolus flower production. The experimental design, using the early maturity cultivar 'White Friendship', was entirely randomized, arranged in a 5 x 2 factorial scheme (five soil water contents: 25; 50;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In Brazil, locations prone to frost have limited climatic conditions for Gladiolus production during this period (Schwab et al, 2018). This is because Gladiolus for commercialization, generating longer floral stems (63.61 cm), a greater number of leaves (6.94) and flowers (9.28), larger diameter (1.15 cm), and reduced cultivation period (57.5 days) (Santos et al, 2020;Mazzini-Guedes et al, 2017).…”
Section: Overall Research Results Indicate That Localmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, locations prone to frost have limited climatic conditions for Gladiolus production during this period (Schwab et al, 2018). This is because Gladiolus for commercialization, generating longer floral stems (63.61 cm), a greater number of leaves (6.94) and flowers (9.28), larger diameter (1.15 cm), and reduced cultivation period (57.5 days) (Santos et al, 2020;Mazzini-Guedes et al, 2017).…”
Section: Overall Research Results Indicate That Localmentioning
confidence: 99%
“…This increase in the number of papers indicates that over the years, there has been a growing interest among researchers in investigating and better describing the behavior and aspects of gladiolus with the aim of optimizing its commercial production. This is because gladiolus is among the most cultivated and traded cut flowers in the world(Mazzini-Guedes et al, 2017) and…”
mentioning
confidence: 99%
“…Although the crop may suffer from excess water, which favors corm rot, induces delayed development cycle and reduces plant growth (PEREIRA et al, 2009;MAZZINI-GUEDES et al, 2017), its highest sensitivity is related to water deficit. Some of the symptoms that can be triggered by water deficit include a shorter development cycle, burned spike tips and reduced growth.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller leaf area can also occur as an adaptation of the plant to water stress conditions, since the decrease in leaf area represents a smaller transpiration surface; thus, avoiding rapid water depletion from soil (Taiz;Zeiger, 2017). When studying the effect of water deficit in gladiolus plants, Mazzini-Guedes et al (2017) observed that plants obtained after applying 25% of field capacity treatment have lower values of total plant height and number of leaves.…”
Section: Resultsmentioning
confidence: 99%